Tantangan Konselor dalam Mengoptimalkan Kinerja Penyandang Disabilitas Guna Meminimalisir Tindak Diskriminasi di Lingkungan Kerja - Muhammad Alridho Lubis; Deby Manalu; Reva Andreani; Rizka Rahmah Gita; Ika Ariyati (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2023)
Because of their physical and mental conditions, people with disabilities are often subject to offensive gossip and are looked down upon by their surrounding communities. To do this, governments need to put policies in place to promote and take into account the rights of persons with disabilities in life activities. One is to optimize disability performance counselors' efforts to avoid discriminatory practices. This article was created to provide an understanding so that readers can educate themselves about disability equality in the workplace. Of course, using the Literature Review and Journal Literature Review methods, data are collected from several journals and articles published in the last decade and accessed via Google Scholar and Publish or Perish.